Analisis Pengendalian Kualitas Menggunakan Metode Statistical Process Control pada Boom Excavator 20 di PT XYZ Batam - Ahmad Rhamadhan; Ansarullah Lawi; Amirah Nova Khairiyah Pane (Fakultas Teknik Universitas Ibnu Sina, 2025)
PT XYZ faces a high defect rate in the production of Boom Excavator 20, particularly in the Hydraulic Mining Shovel (HMS) component. This study aims to identify the causes of defects and provide recommendations for quality improvement using the Statistical Process Control (SPC) method. Data from August 2023 to July 2024 were collected and analyzed using SPC tools, including check sheets, control charts, Pareto diagrams, histograms, and cause-and-effect diagrams. The results revealed that spatter and material damage were the most common defects. Analysis identified four main contributing factors: poor electrode quality, operator skill and errors, improper welding methods, and unstable welding machines. Based on these findings, the study recommends improving electrode quality control, enhancing operator training, optimizing welding techniques, and performing regular machine maintenance. This research demonstrates the effectiveness of SPC in monitoring and improving the quality control processes of PT XYZ.